Identifying ignitable liquids in fire debris : a guideline for forensic experts - Hendrikse, Jeanet; Grutters, Michiel; Schafer, Frank (London : Academic Press, an imprint of Elsevier, 2016)
Identifying Ignitable Liquids in Fire Debris - A guideline for forensic experts - discusses, and in particular, illustrates the characteristics of different ignitable liquid products in detail. This guideline builds on the minimum criteria of the ignitable liquid classes defined in the internationally accepted standard ASTM E1618 Standard Test Method for Ignitable Liquid Residues in Extracts from Fire Debris Samples by Gas Chromatography-Mass Spectrometry. It provides information on the origin of the characteristics of these ignitable liquid products and gives a summary of characteristics which should be demonstrated for a positive identification of the particular product class. Topics such as i) the term ignitable liquid, ii) relevant guidelines for fire debris analysis, iii) production processes of ignitable liquids, iv) fire debris analysis methods, and v) interferences in fire debris analysis, are briefly discussed as these topics are essential for the understanding of the identification and classification of ignitable liquid residues in fire debris.
6.3.3.3 Composition of Conventional MPD Compared to De-Aromatized MPD6.3.3.4 Composition of Conventional MPD Compared to Dewaxed MPD; 6.3.3.5 Effects that Alter the Composition of MPD; 6.3.3.5.1 Partial Evaporation; 6.3.3.5.2 Microbial Degradation; 6.3.3.6 Summary of Characteristics for the Identification of MPD; 6.3.4 Heavy Petroleum Distillates; 6.3.4.1 Introduction; 6.3.4.2 Overall Composition of HPD; 6.3.4.3 Composition of Conventional HPD Compared to De-Aromatized HPD; 6.3.4.4 Composition of Conventional HPD Compared to Dewaxed HPD
Includes bibliographical references.
Online resource; title from PDF title page (EBSCO, viewed October 8, 2015).
Elsevier
Keywords: Flammable liquids; Flammable liquids -- Identification; Fire investigation; Forensic sciences; TECHNOLOGY & ENGINEERING / Mechanical; Fire investigation; Flammable liquids; Forensic sciences; Electronic books; Guidebooks; Electronic books